Novel phenolic antimicrobials enhanced activity of iminodiacetate prodrugs against biofilm and planktonic bacteria. (22nd September 2020) - Walsh, Danica J.; Livinghouse, Tom; Durling, Greg M.; Arnold, Adrienne D.; Brasier, Whitney; Berry, Luke; Goeres, Darla M.; Stewart, Philip S.
Abstract: Prodrugs are pharmacologically attenuated derivatives of drugs that undergo bioconversion into the active compound once reaching the targeted site, thereby maximizing their efficiency. This strategy has been implemented in pharmaceuticals to overcome obstacles related to absorption, distribution, and metabolism, as well as with intracellular dyes to ensure concentration within cells. In this study, we provide the first examples of a prodrug strategy that can be applied to simple phenolic antimicrobials to increase their potency against mature biofilms. The addition of (acetoxy)methyl iminodiacetate groups increases the otherwise modest potency of simple phenols. Biofilm‐forming bacteria exhibit a heightened tolerance toward antimicrobial agents, thereby accentuating the need for new antibiotics as well as those, which incorporate novel delivery strategies to enhance activity toward biofilms. Abstract : Biofilms present significant health concerns, contributing to chronic infections and contamination across diverse settings. A pro‐drug approach using (acetoxy) methyl iminodiacetates has markedly enhanced the activity of classical phenolic antimicrobials.